Proceedings. Second International Conference on Creating, Connecting and Collaborating Through Computing
DOI: 10.1109/have.2004.1391881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating haptics and 3D stereo displays using Fitts' law

Abstract: This poper describes research pe$onned at the BioRobotics lab ai Stanford Universify on the development of a visio-haptic workstation for surgical simulation. This study focuses on the design trodeoffs and choices that must be mode to successfilly combine 3 0 stereo with haptic feedback lo enoble immersive interaction with simulated surgicol environments. Specifically, the study concentrates on building a matrix for evaluating 3 0 stereo haptic workstations. This research attempts to make quantitative comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The effects of haptic feedback on user performance have been documented in previous studies, e.g., [46,[56][57][58]65]. Other research has shown that haptic feedback improves user performance for 3D pointing in VR over no feedback [35,42]. Overall, these VR studies yield a broad indication that haptic feedback can increase user performance in VE [11,42], and further work has proposed to use haptic feedback as an assistance system [29,42].…”
Section: Haptic Feedback and Interaction In Vrmentioning
confidence: 53%
“…The effects of haptic feedback on user performance have been documented in previous studies, e.g., [46,[56][57][58]65]. Other research has shown that haptic feedback improves user performance for 3D pointing in VR over no feedback [35,42]. Overall, these VR studies yield a broad indication that haptic feedback can increase user performance in VE [11,42], and further work has proposed to use haptic feedback as an assistance system [29,42].…”
Section: Haptic Feedback and Interaction In Vrmentioning
confidence: 53%
“…Results in time performance indicate the Drag and Follow techniques had the greater amount of time elapsed by the users. This might be due that this techniques required pointing towards the desired contact area [28,32] and Fitts' Law [7,14,16,25] as shown in the research of Bruder et al [9] and Chun et al [22]. In addition, the presented shapes had also different levels of complexity in the coloring task.…”
Section: Discussionmentioning
confidence: 99%
“…The HMD gave the worst result in both the experimental task and the SSQ assessment due to the accompanied discomfort and fatigue. Chun et al [6] considered that it may be due to its limited configuration where the resolution is only 800×600 pixels with a small field of view. In all conditions, movement time increased linearly with levels of IDs.…”
Section: Discussionmentioning
confidence: 99%
“…Fitts' pointing paradigm is a visually-controlled task, hence either input devices or display devices could influence performance of human motor system. In order to test whether Fitts' Law is applicable to compare display devices, Chun et al [6] used Fitts' Law to evaluate four 3D stereo displays with same haptic input device. The results of this study demonstrated that Fitts' Law was applicable to the evaluation of visio-hoptic workstations.…”
Section: Introductionmentioning
confidence: 99%